Use of Equine Pituitary Extract (EPE) in low doses to induce double ovulation in mares - Ferreira Sá, Marcus André; De Oliveira Santos, Gabriel; Bezerra, Luciana Lima; Moreno, Marcela Poerner; Barbosa, Celso Guimarães; Alvarenga, Marco Antônio [UNESP]; Jacob, Júlio César Ferraz (Revista Brasileira de Medicina Veterinaria, 2017)
The aim of this study was to evaluate the effect of treatment using low doses of EPE on rates of ovulation and embryo recovery. Eight mares were used in this way: first cycle (n = 8)-control group (untreated); second cycle (n = 8)-treated group using 8.0 mg of EPE, bid, until at least two follicles reached =35 mm diameter. At this moment, was administered 1000 IU hCG, E.V., as ovulation agent. The embryos recovery were performed eight days after detection of second ovulation. Mares received 5.0 mg PGF2a, I.M. On D8. The percentage of mares that showed two or more ovulations was higher (p <0.01) for the treated group (7/8, 87.5%) than the control group (1/8, 12.5%). The rate of recovered embryos per ovulation did not show statistical difference (P>0.05) between the treated (11/16, 68.8%) and control (6/9, 66.6%) groups. The results of this study allow concluding that treatment using low doses of EPE increased the incidence of multiple ovulations and provided greater recovery embryos rate.
Keywords: Embryo recovery; Multiple ovulations; Ovarian physiology; Ovulation rate